ANALISIS STRATEGI POSITIONING UNIVERSITAS HANG TUAH ( Blue Ocean Campus ) - Herman (Faculty of Social and Political Science, 2015)
This research aimed to analyze the positioning strategy of Hang Tuah University Surabaya in the minds of customers, by analyzing the slogan